2010
DOI: 10.1016/j.ijrobp.2009.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Dose–Volume Effects on Salivary Gland Function

Abstract: Publications relating parotid dose-volume characteristics to radiotherapy-induced salivary toxicity were reviewed. Late salivary dysfunction has been correlated to the mean parotid gland dose, with recovery occurring with time. Severe xerostomia (defined as long-term salivary function of <25% of baseline) is usually avoided if at least one parotid gland is spared to a mean dose of less than ≈20 Gy or if both glands are spared to less than ≈25 Gy (mean dose). For complex, partial-volume RT patterns (e.g., inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
406
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(433 citation statements)
references
References 30 publications
11
406
2
7
Order By: Relevance
“…Most of the previous studies reported on anatomic and dosimetric changes of the PG. This trend of study can be explained by the fact that radiation dosimetric changes for PGs are associated with saliva reduction and xerostomia 29, 30, 31…”
Section: Discussionmentioning
confidence: 97%
“…Most of the previous studies reported on anatomic and dosimetric changes of the PG. This trend of study can be explained by the fact that radiation dosimetric changes for PGs are associated with saliva reduction and xerostomia 29, 30, 31…”
Section: Discussionmentioning
confidence: 97%
“…They were defined prior to commencement of the AP evaluation. The OAR score values are based on biological endpoints 20 , 21 , 22 , 23 and attempt to capture the physician's perception of the relative importance of different dose goals. Taking the parotid gland as an example, the maximum available score is 15, relative to the target coverage maximum score of 25.…”
Section: Methodsmentioning
confidence: 99%
“…One major area of concern for head and neck treatments is the dosimetric sparing of a patient's salivary glands, pharyngeal constrictors, and larynx. High doses of radiation to these organs can cause dry mouth (xerostomia) and difficulty swallowing (dysphagia) 2, 3, 4, 5, 6. Sparing a patient's salivary glands and larynx has been shown to reduce symptoms and increase patient quality of life 2, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Sparing a patient's salivary glands and larynx has been shown to reduce symptoms and increase patient quality of life 2, 7, 8, 9. The QUANTEC review of dose–volume effects on salivary function by Deasy et al concluded that for IMRT plans the mean dose to each parotid gland should be kept as low as possible 3. It also states that, “a lower mean dose to the parotid gland usually results in better function, even for relatively low mean doses (<1000 cGy).”3 The same review examining larynx and pharynx dose–volume effects had a similar conclusion stating that planners should minimize the volume of pharyngeal constrictors and larynx receiving 6000 cGy, and when, possible 5000 cGy 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation